The Lean Business Guidebook How to Satisfy Your Customers and Maximize Your Profit. - Bindra, M. J. S.; Kaur, Ekroop (Milton : Productivity Press, 2022)
This book introduces a powerful system that explains how to run a company with a focus on continuous improvement. The results are a satisfied customer base, evolving products and an increase in revenue and profits. These factors determine the success for any company because business transformation involves making fundamental changes in how business is conducted to cope with shifts in the market environment. This a comprehensive book for valuable guidance on framing strategy and overcoming challenges for successful and sustainable implementation of a lean production system, daily management system and lean accounting system in companies to empower the managers to serve their customers with timely delivery of quality products while maximizing profits and easing workloads. The main challenge is ensuring operations colleagues in different functions understand the link between their daily work and the profit and loss statement. In addition, it illustrates how finance personnel can assist the operations team and be a part of the transformation journey. This book is not meant to impart theoretical knowledge of the lean production system, daily management and lean accounting, as there are many books already available that focus on the methodology instead of the implementation. This book empowers people in each function of a company, irrespective of which level they work in the company, and shows them the way to operate on a daily basis to achieve the company's strategy while simultaneously fulfilling their career goals. The book lays out a brief history of the evolution of lean concepts with a focus on lean accounting. This book guides the successful implementation and sustenance of lean and kaizen tools and provides answers to the questions: Who should lead the lean and kaizen implementation in the company? Where should the lean and kaizen journey begin? Which lean and kaizen tools should be implemented first? How important is capacity for the company? How much current capacity is wasted and how much free capacity is available? Where exactly are the resources being wasted in the company? How can the company reduce waste to release capacity for more production? Why should the daily management system and lean accounting system be implemented simultaneously with the lean production system? Why must managers understand the monetary value of their daily activities? Is there an easy way of making a profit and loss statement that is understood at each level in the company? Why is one-day closing of accounts important and how can it be done?
9.4 How Value Stream Managers and Functional Managers Use the Corporate Scorecard -- 10 Lean Performance Measurement System -- 10.1 Need for the Lean Performance Measurement System -- 10.2 Lean Performance Measurement System Framework -- 10.3 Implementation of the Lean Performance Measurement System -- 10.4 How Should Employees at Every Level Utilize Their Time in a Lean Company? -- 11 Finance for Non-Finance -- 11.1 How Much Do Your Managers Know About the Finance of the Company? -- 11.2 Bonding with the Profit and Loss Statement -- 11.3 Key Performance Responsibilities of Functional Managers
Description based upon print version of record.
12 New Role of Finance Team.
OCLC-licensed vendor bibliographic record.
Keywords: Business planning; Strategic planning; Industrial efficiency; Organizational effectiveness; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Management